China's Military Procurement in the Reform Era : The Setting of New Directions - Evron, Yoram (Lahore Service Book Club)
The decisions that shape the policy of weapons procurement are an important area of national security policy. This is all the more true for China, which during recent decades has vacillated between different sources and directions of military build-up. This book explores the politics of military procurement in China under the successive leaderships of Deng Xiaoping, Jiang Zemin and Hu Jintao. It shows how China's political and military leaders have sought to adjust military procurement policy to meet China's strategic objectives, to relate it to non-military needs, to strike a balance between
Include Bibliography
Keywords: Military policy -- China -- Armed Forces--Weapons systems -- Armed Forces--Procurement